Pemberian Edukasi Gosok Gigi di PAUD Mawar - Esti Rahayu; Hikmatul Khoiriyah; Meri Liandani; Haidir (LPPM UNINUS, 2025)
This community service activity aims to improve the knowledge and skills of young children in maintaining dental health through education on proper tooth brushing at Mawar Preschool (PAUD Mawar). Dental health education is crucial from an early age given the high caries rate among preschool children in Indonesia. This activity involved 25 students aged 3–6 years old, using a participatory approach that included counseling, demonstrations of tooth brushing techniques, and hands-on practice. The activity included planning, implementation, and monitoring and evaluation to assess the children's understanding and skills. The results showed an increase in knowledge about tooth brushing times and the importance of maintaining dental hygiene. 92% of students were able to correctly answer the questions after the education session. Furthermore, 84% of students were able to practice proper tooth brushing techniques based on observations during the practice. Teachers and parents responded positively and expressed their readiness to support ongoing tooth brushing habits. Thus, this activity successfully increased children's awareness and skills in maintaining dental hygiene and strengthened collaboration between the school, parents, and healthcare professionals. Keywords: dental health education, early childhood, tooth brushing practice, Mawar Preschool, community empowerment.